Sex-Related Differential Prevalence of Central Obesity in Diabetes Mellitus: A Multi-centred Survey in North-Central Nigeria - Mshelia-Reng R; Lawal Y; Odiase SO; Shuaibu R; Odumodu K; Anumah FE (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2023)
Background: Contrary to the old dictum that central obesity is more common among men than women, recent reports have shown a gradual reversal of this trend, as suggested by some studies. Objective: To compare the prevalence of central obesity among men and women with Diabetes mellitus in North-Central Nigeria. Methods: This multi-centred, cross-sectional study was conducted across 20 hospitals in Abuja, Nasarawa State, and Niger State, involving 1040 participants. Some obesity indices (body mass index, waist circumference and waist-to-height ratio) were measured. Results: The prevalence of central obesity (waist circumference criterion) was significantly higher in the females compared to male participants (89.6% vs 51.6%, χ2 = 1231.37, p<0.001), similar to the prevalence determined by waist-height ratio criterion (female vs male, 88.8% vs 71.5%, χ2 = 58.83, p<0.001). Following correction for age, duration of diabetes mellitus, blood pressure, blood glucose, and glycated haemoglobin using logistic regression, female gender remained a significant determinant of central obesity (OR = 2.76, 95% CI 1.81-3.83, p = 0.004). Conclusion: The prevalence of central obesity was higher among women than men in a cross-section of patients with diabetes mellitus in North-Central Nigeria.